2022
DOI: 10.1007/s10967-022-08189-1
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade of recommended nuclear cross section data base for production of therapeutic radionuclides

Abstract: The IAEA Nuclear Data Section has coordinated several actions to setup and improve a database for recommended cross sections and nuclear decay data for various charged-particle reactions that can be used for medical radionuclide production. Some of the earlier evaluations did not provide uncertainties for the recommended cross sections. Updated evaluations with uncertainty quantification for 25 reactions relevant for production of 67Cu, 103Pd, 102mgRh, 114mIn, 125I, 169Yb, 177gLu, 186Re, 192Ir and 210,211At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 105 publications
(205 reference statements)
0
2
0
Order By: Relevance
“…It is evident that those two evaluations are not fully supported by the new data. In particular the updated curve (Tárkányi et al, 2022) appears to be too low. Considering all the data published we conclude that a new evaluation is necessary using the theoryassisted selection of data.…”
Section: Therapeutic Radionuclide 67 Cumentioning
confidence: 95%
See 1 more Smart Citation
“…It is evident that those two evaluations are not fully supported by the new data. In particular the updated curve (Tárkányi et al, 2022) appears to be too low. Considering all the data published we conclude that a new evaluation is necessary using the theoryassisted selection of data.…”
Section: Therapeutic Radionuclide 67 Cumentioning
confidence: 95%
“…The standardisation of production cross sections was attempted under an IAEA-CRP (Qaim et al, 2011). Another IAEA-CRP version has also been presented (Tárkányi et al, 2022). Jung et al (2023) reported extensive new cross-section measurements in the higher energy range.…”
Section: Therapeutic Radionuclide 67 Cumentioning
confidence: 99%
“… Comprehensive presentation of experimental data and TENDL predictions for the 103 Rh(p,n) 103 Pd reaction [ 25 ] (with permission). …”
Section: Methodsmentioning
confidence: 99%
“…The relative intensities were obtained as a weighted average of values from about 107 individual measurements. For example, the measured I(rel) values for one of the strongest 656.008-keV  ray range between 63(8) and 87 (8), relative to I(rel) = 100 for the 282.956-keV  ray, with a reported weighted average value of I(rel) = 79.3 (10) (see Table 3 and Ref. [20]).…”
Section: Review Of Decay Data For 61 Cu Fg Kondevmentioning
confidence: 99%